Dynastic Entrepreneurship, Entry, and Non-Compete Enforcement - James E. Rauch (Center for Economic Studies and ifo Institute (CESifo), 2015)
We investigate entry in a dynastic entrepreneurship (overlapping generations) environment created by employee spinoffs. Without finance constraints, enforcement of non-compete agreements unambiguously improves social welfare outcomes, and even increases the rate of spinoffs from original firms. Indeed, if employers have all the bargaining power vis-à-vis their employees, optimal entry of original firms and all subsequent employee spinoffs is achieved, despite the fact that the original firm can only negotiate with the first spinoff. However, if employees are unable to buy out their non-compete contracts, enforcement of these agreements shuts down socially profitable spinoff firms. Non-enforcement sacrifices entry of original firms that would be marginally profitable in the absence of employee spinoffs, but otherwise clearly improves social welfare outcomes over enforcement in the presence of finance constraints.
Keywords: K12; L26; 330; entrepreneurship; entry; finance constraints; non-competes; overlapping generations; spinoffs